Strategi Transformasi Digital LPP TVRI - Tereuri, Shabrina; Azhari Rangkuti, Herry; Satria, Riri; Lusa, Sofian (Rifa'Institute, 2022)
The television industry is undergoing a digital revolution. Infrastructure-based broadcast services with linear programs in the form of news, sports and entertainment broadcasts at certain times, have experienced the disruption of video streaming and on-demand viewing services based on digital platforms. TVRI as a public broadcasting institution also suffered a similar blow. With the mission of providing television broadcasting services to all corners of the archipelago, TVRI must maintain a balance playing in linear programming to be able to reach remote areas that have not been reached by digital platforms, and definitely digitally transform to secure its position in the TV and video industry market. To be able to digitally transform LPP TVRI requires the right strategy to be able to successfully survive market changes and still be able to carry out the government's mission to deliver TV broadcasts to all corners of the archipelago. This study aims to formulate a digital transformation strategy of LPP TVRI from traditional TV to digital to digitally capable TV. Based on the research conducted, it can be concluded that to develop a strategy in implementing digital transformation, among others, by developing a digital strategy using the framework owned by Sunil Gupta. After that, it can be concluded that the developed digital strategy focuses on building new capabilities, namely to make TVRI a Digital Broadcaster. By applying the Freemium model to certain content